Evaluation of trace metal speciation and bioavailability in anaerobic systems - Pham, Minh Thanh (2017)
The importance of trace metals in anaerobic reactors has already been acknowledged in the literature, however, their bioavailability for microbial uptake which is governed by their speciation, has been poorly understood. There was a lack of information about the interaction between trace metals and organic/inorganic ligands and the operational parameters that affect their speciation in an anaerobic bioreactor. Therefore, the main objectives of this thesis were to investigate the speciation and bioavailability of trace metals in submerged anaerobic membrane bioreactors (SAMBRs) under the following conditions: in the presence of sulfide; with the addition of biodegradable chelating agent EDDS; under nutrient deficiency; under organic shock loads; and under changes in operating parameters i.e. pH, hydraulic retention time (HRT), and solids retention time (SRT). The results showed that acetoclastic methanogens were more constrained by Fe2+ limitations compared to other trophic groups, while an organic shock resulted in leaching of Fe2+ from the residual to organically bound and soluble forms, and the precipitation of Fe2+ as a sulfide salt seemed to reduce its bioavailability to acetoclastic methanogens. Biodegradable chelating agent EDDS when dosed as a metal complex with Fe2+ was able to compete with sulfide and keep the Fe2+ in a soluble form as an Fe-EDDS complex, hence improving the performance of the SAMBR. Characterization of different EDDS forms by Ultra-Fast Liquid Chromatography (UHPLC) showed the presence of free EDDS and Fe-EDDS complex, and chromatographic analyses confirmed the increase in the Fe soluble fraction. Organic shocks (glucose spikes) applied to the SAMBR resulted in leaching of Fe from residual to soluble and organically bound forms. The supplementation of Fe helped to remove the VFAs accumulated during the organic shocks. SAMBR performance was significantly affected by the low pH (6) and HRT (2 h), but it was still able to achieve high treatment efficiencies at low SRTs (25 d). The reduction in these parameters all resulted in a decrease in metal content in the SAMBR, and the degree of trace metal loss from the SAMBR varied between metals as it depends on the sensitivity of the trace metals towards the changes, and also their affinity to anaerobic sludge. In all changes of each operating parameter, the trend in speciation of the trace metals generally tended to a shift towards highly bioavailable fractions.